Prg4 and Osteoarthritis: Functions, Regulatory Factors, and Treatment Strategies - Peng-Jie Fu; Sheng-Yuan Zheng; Yan Luo; Zhuo-Qun Ren; Zi-Han Li; Ya-Ping Wang; Bang-Bao Lu (Biomedicines)
Proteoglycan 4 (PRG4), also known as lubricin, plays a critical role in maintaining joint homeostasis by reducing friction between articular cartilage surfaces and preventing cartilage degradation. Its deficiency leads to early-onset osteoarthritis (OA), while overexpression can protect against cartilage degeneration. Beyond its lubricating properties, PRG4 exerts anti-inflammatory effects by interacting with Toll-like receptors, modulating inflammatory responses within the joint. The expression of Prg4 is regulated by various factors, including mechanical stimuli, inflammatory cytokines, transcription factors such as Creb5 and FoxO, and signaling pathways like TGF-β, EGFR, and Wnt/β-catenin. Therapeutic strategies targeting PRG4 in OA have shown promising results, including recombinant PRG4 protein injections, gene therapies, and small molecules that enhance endogenous Prg4 expression or mimic its function. Further research into the molecular mechanisms regulating Prg4 expression will be essential in developing more effective OA treatments. Understanding the interplay between Prg4 and other signaling pathways could reveal novel therapeutic targets. Additionally, advancements in gene therapy and biomaterials designed to deliver PRG4 in a controlled manner may hold potential for the long-term management of OA, improving patient outcomes and delaying disease progression.